Civil Society As Constitutional Guardians: Comparative Analysis And Indonesian Prospects: Masyarakat Sipil sebagai Penjaga Konstitusi: Analisis Perbandingan dan Prospek Indonesia - M. Reza Saputra (Yayasan Cerdas Pedia Indonesia, 2025)
This study examines civil society organizations (CSOs) as constitutional guardians in Indonesia through comparative constitutional analysis. Although prior scholarship has documented procedural aspects of constitutional complaints, the participatory dynamics through which CSOs strengthen constitutional accountability remain underexplored. Employing normative legal-juridical methodology and comparative law analysis, this research examines CSO engagement models in South Korea, South Africa, and Germany to derive lessons for Indonesia's constitutional system. The study identifies institutional and procedural barriers impeding optimal CSO participation, including limited legal standing and high access costs. Empirical findings demonstrate that CSOs significantly influence constitutional courts by expanding access to justice, contributing expertise, and catalyzing jurisprudential innovation. In Indonesia, the emerging amicus curiae practice signals potential for deeper CSO involvement; however, structural constraints remain. This study concludes that comprehensive institutional reform is imperative. Key recommendations include formalizing CSO standing through Constitutional Court Law amendments and lowering access barriers to strengthen participatory democracy and safeguard citizens' constitutional rights.